2021
DOI: 10.3390/diagnostics11091537
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Type 1 Diabetes Mellitus. Report 4: Glycated Haemoglobin

Abstract: The purpose of this study was to evaluate specifically the relationship between glycated haemoglobin (HbA1c) levels and retinal optical coherence tomography (OCT) and OCT angiography (OCTA) parameters in type 1 Diabetes Mellitus (DM). A total of 478 type 1 DM patients and 115 controls were included in a prospective OCTA trial (ClinicalTrials.gov NCT03422965). Subgroup analysis was performed for controls, no diabetic retinopathy (DM-no DR) and DR patients (DM-DR), and HbA1c levels. OCT and OCTA measurements wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, this also confers high internal validity because it is allegedly the largest type 1 DM retinal imaging dataset of the literature. 38 , 39 , 40 Second, control and DM groups differed in some baseline characteristics, such as age, smoking status, and body mass index, which may have influenced the results. Third, for OCT images, only a single B scan centered in the fovea has been used to extract the radiomics features, when each macular cube scan consists of 128 consecutive B scans, which could potentially under or overestimate the results reported either way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this also confers high internal validity because it is allegedly the largest type 1 DM retinal imaging dataset of the literature. 38 , 39 , 40 Second, control and DM groups differed in some baseline characteristics, such as age, smoking status, and body mass index, which may have influenced the results. Third, for OCT images, only a single B scan centered in the fovea has been used to extract the radiomics features, when each macular cube scan consists of 128 consecutive B scans, which could potentially under or overestimate the results reported either way.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 593 individuals with retinal images corresponding to 1186 eyes and ocular and systemic data were recruited, 478 patients with type 1 DM (n = 956 eyes) and 115 healthy controls (n = 230 eyes). Systemic, ocular, and retinal images quality exclusion criteria were applied as described elsewhere 39 , 40 41 and 439 individuals (n = 726 eyes) with a complete battery of all retinal images constituted the primary dataset for analysis. To evaluate the influence of a potential bilaterality bias, a secondary analysis was conducted by randomly selecting only 1 eye per patient (1 eye/1 patient) that included 439 patients (n = 439 eyes).…”
Section: Methodsmentioning
confidence: 99%
“…One of the most clinically relevant findings of this study is the identification of FAZc as a potential indirect biomarker of DKD progression. The status of the FAZ and its different parameters, such as area, perimeter or circularity, has been previously described as a marker associated with DR stage [ 9 , 15 , 18 ], a surrogate marker of VA [ 40 ] or associated to HbA1c levels [ 24 ]. With regard to kidney function, some previous reports have described an association between FAZa and GFR [ 13 ] or ACR [ 27 ], although other authors have not found any association between these parameters [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography angiography (OCTA) [ 6 ] is a newly developed, non-invasive, retinal imaging technique that allows objective quantification of microvascular parameters in the perifoveal vascular network, such as vessel density or flow impairment areas [ 7 , 8 ]. Recent studies have analyzed the relationship between OCTA and DR stage [ 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and systemic markers of disease, such as glycated hemoglobin levels [ 24 ]. Since this technique allows direct noninvasive in vivo visualization of the microvascular circulation, it is sensible to think that the detection of microvascular changes may be associated to other clinical manifestations elsewhere in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have made evident that OCTA measurements of the microvasculature may differ based on age [153][154][155], sex [156,157], HbA1c levels [102,158,159], and a variety of other systemic or metabolic vascular risk factors [160][161][162][163]. Additionally, previous work by Chun et al illuminated differences in OCTA quantitative parameters between healthy, young Black and White patients [164].…”
Section: Limitations and Shortcomings Of Oct Angiography In Quantitative Analysismentioning
confidence: 99%